Health education about asthma in Arang Limbung Village, Kubu Raya Regency - Lestari Makmuariana; Wida Kuswida Bhakti; Surtikanti Surtikanti; Riska Maulidia; Okkyandi Adikarsa; Muhammad Alfarizi; Robi Robiansyah; Nanda Adia Agustin; Nurmalinda Nurmalinda; Herinawan Herinawan; Murni Murni; Puja Puja; Siti Juwariyah (Community Empowerment, 2023)
Asthma is an inflammatory disease of the respiratory system that can be triggered by several factors such as the environment, food, air, and emotions. The increase in asthma sufferers is due to a lack of knowledge about how to prevent asthma. The purpose of this activity is to increase knowledge so that people with asthma can be more aware of asthma prevention. The implementation method in community service uses the target group survey method, preparation of facilities and infrastructure, outreach, and evaluation. Based on the program, 98% of the participants seemed enthusiastic about obtaining information about asthma, and 100% of the participants seemed satisfied with the results of the discussion about asthma.